Effect of Parking Policy Parameters on Patronizing Public Transport - Patitapaban Panda, Sudhanshu Sekhar Das (International Journal of Control and Automation, 2020)
The parking policy for patronizing public transport can be finalized based on the behavioural analysis of trip makers using personal vehicle. Effect of different attributes of parking policy guideline for patronizing public transport is discussed in this paper. In developing countries like India, the sudden increase in private vehicle ownership with an increase in the economy leads to a lot of urban transportation problems. Properly designed sensible parking policy can optimize the road space efficiency allowing citizens to perform all social and economic activities patronizing public transport for improvement in their mobility. The effect of selected attributes like parking type, parking duration, parking location, and parking price on measures of effectiveness are examined. Finally, a comparison of selected attributes affecting the parking policy is made. It is observed that ‘Parking Cost’, ‘Parking Access and Egress Distance’, ‘Parking Type’ and ‘Parking Duration’ has significant effect on patronage of public transport. These parameters can be taken in combination to formulate a parking policy in consultation with policy makers.